Delineating the Mechanism of Ionic Liquids in the Synthesis of Quinazoline‐2, 4(1H, 3H)‐dione from 2‐Aminobenzonitrile and CO2. (26th July 2017) - Hulla, Martin; Chamam, Sami M. A.; Laurenczy, Gabor; Das, Shoubhik; Dyson, Paul J.
Abstract: Ionic liquids (ILs) are versatile solvents and catalysts for the synthesis of quinazoline‐2, 4‐dione from 2‐aminobenzonitrile and CO2 . However, the role of the IL in this reaction is poorly understood. Consequently, we investigated this reaction and showed that the IL cation does not play a significant role in the activation of the substrates, and instead plays a secondary role in controlling the physical properties of the IL. A linear relationship between the p K a of the IL anion (conjugate acid) and the reaction rate was identified with maximum catalyst efficiency observed at a p K a of >14.7 in DMSO. The base‐catalyzed reaction is limited by the acidity of the quinazoline‐2, 4‐dione product, which is deprotonated by more basic catalysts, leading to the formation of the quinazolide anion (conjugate acid p K a 14.7). Neutralization of the original catalyst and formation of the quinazolide anion catalyst leads to the observed reaction limit.